2010
DOI: 10.1016/j.enzmictec.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Electricity generation from carbon monoxide in a single chamber microbial fuel cell

Abstract: Electricity generation from carbon monoxide in a single chamber microbial fuel cell Mehta, P.; Hussain, A.; Tartakovsky, B.; Neburchilov, V.; Raghavan, V.; Wang, H.; Guiot, S. R.Contact us / Contactez nous: nparc.cisti@nrc-cnrc.gc.ca. READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Enzyme and Microbial Technology 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 21 publications
5
60
2
Order By: Relevance
“…Nevertheless, an optimum operation of an MFC requires that the rate of gas transfer matches the rate of its consumption. Mehta et al (2010) observed a CO consumption rate of 2.1 L (L R day) −1 for an MFC equipped with a sparger, i.e., providing a sufficient membrane area, the K L a values obtained in our tests were sufficient to match the observed CO consumption. Excessive CO transfer might lead to CO-related inhibition of carboxidotrophic organisms (Henstra et al 2007;Sipma et al 2006;Sokolova et al 2009).…”
Section: Membrane Systems For Improved Mass Transfer Efficiencymentioning
confidence: 49%
See 4 more Smart Citations
“…Nevertheless, an optimum operation of an MFC requires that the rate of gas transfer matches the rate of its consumption. Mehta et al (2010) observed a CO consumption rate of 2.1 L (L R day) −1 for an MFC equipped with a sparger, i.e., providing a sufficient membrane area, the K L a values obtained in our tests were sufficient to match the observed CO consumption. Excessive CO transfer might lead to CO-related inhibition of carboxidotrophic organisms (Henstra et al 2007;Sipma et al 2006;Sokolova et al 2009).…”
Section: Membrane Systems For Improved Mass Transfer Efficiencymentioning
confidence: 49%
“…1). The work of Mehta et al (2010) also raised a possibility of another pathway, which involved direct electron transfer to the anode by metal-reducing carboxidotrophic bacteria (pathway 5 in Fig. 1).…”
Section: Microbial Community Of a Syngas-fed Mfcmentioning
confidence: 99%
See 3 more Smart Citations